English for Tourism for the Tourism Village Pioneer in Tlogobulu, Kaligesing, Purworejo - Zulia Chasanah; Sudar Sudar; Semi Sukarni (Universitas Muhammadiyah Purworejo, 2022)
This paper aims to develop English language skills, especially due to tourism. Based on the theme, the team of Lecturers in English Language Education, Purworejo Muhammadiyah University presents material on learning English, especially in the field of tourism in the village of Tlogobulu, Kaligesing, Purworejo, especially the community of Tlogobulu Village, Kaligesing, Purworejo, especially the community. In Purworejo regency, there are several tourism locations that have the potential to be developed to the national, even international level. In addition, to drive the economic potential of the tourism sector from upstream to downstream, it is very important to empower the tourism potential in the village area. Therefore, the english education lecturer's community service team in collaboration with the village head of Tlogobulu, Kaligesing subdistrict, Purworejo, organized an activity with the theme ‘’English for Tourism for the Tourism Village Pioneer”. Thus the participants gained new experiences, especially about Tourism English skills. The material they obtained from the English Lecturer team is as follows; (1)